Severe parapharyngeal abscess that developed significant complications: management during the COVID-19 pandemic. Issue 12 (22nd December 2020) - Ajeigbe, Teslimat; Ria, Basmal; Wates, Emma; Mattine, Samuel
Abstract : A 50-year-old Caucasian man presented to the emergency department during the early stages of the COVID-19 pandemic with a rapidly progressive facial swelling, fever, malaise and myalgia. The patient had recently travelled to a COVID-19-prevalent European country and was therefore treated as COVID-19 suspect. The day before, the patient sustained a burn to his left forearm after falling unconscious next to a radiator. A CT neck and thorax showed a parapharyngeal abscess, which was surgically drained, and the patient was discharged following an intensive care admission. He then developed mediastinitis 3 weeks post-discharge which required readmission and transfer to a cardiothoracic unit for surgical drainage. This report discusses the evolution of a deep neck space infection into a mediastinitis, a rare and life-threatening complication, despite early surgical drainage. This report also highlights the difficulties faced with managing patients during the COVID-19 pandemic.